Thyroid Status During Pregnancy in Women With Polycystic Ovary Syndrome and the Effect of Metformin - Trouva, Anastasia; Alvarsson, Michael; Calissendorff, Jan; Åsvold, Bjørn Olav; Vanky, Eszter; Hirschberg, Angelica Lindén (Frontiers in Endocrinology, 2022)
Objective Polycystic ovary syndrome (PCOS) and hypothyroidism are related conditions, and both are associated with adverse pregnancy outcomes. Knowledge is lacking about the complex interaction between thyroid status and PCOS during pregnancy. We investigated the thyroid status and its association with pregnancy complications in PCOS, and in relation to metformin treatment. Design Post-hoc analyses of two randomized, double-blind, placebo-controlled trials. Methods 288 pregnant women with PCOS were randomized to treatment with metformin or placebo from first trimester to delivery. We measured serum levels of thyroid stimulating hormone (TSH) and free thyroxine (fT4) at gestational week (gw) 5-12, 19, 32 and 36 and related to metformin treatment and pregnancy complications. Thyroid peroxidase antibodies (TPO-ab) were analyzed at inclusion and at gw 36. Results The overall prevalence of subclinical and overt hypothyroidism was 1.5% and 0%, respectively. The TSH level was not affected by metformin, whereas fT4 was significantly higher in the metformin group with less decrease throughout pregnancy compared to placebo, p<0.001. A lower decrease in fT4 during pregnancy correlated to less weight gain (r= -0.17, p=0.020) and tended to be associated with reduced odds ratio for gestational diabetes (OR 0.85 per 1 pmol/L, 95% CI 0.71;1.02). Conclusions In women with PCOS, metformin treatment during pregnancy was associated with less decrease in fT4 compared to placebo, while it did not affect TSH. A smaller decrease in fT4 correlated to less weight gain and tended to be associated with a lower risk of gestational diabetes. Clinical Trial Registration ClinicalTrials.gov, identifier NCT00159536 (The PregMet study); identifier NCT03259919 (The pilot study).